Shakespeare & Hathaway : private investigators. Season four [videorecording (DVD)] - Thompson, Paul Matthew; Tindall, Jude (BBC Studios, 2022)
"From suspected ghosts to the torrid world of Shakespearian escorts, not to mention the fiendish passions and bitter rivalries of ballroom dancing, it's business as usual for the debt-laden ex-policeman and his much more credible partner-in-crime. And the pair also have demons of their own to wrestle with - Lu joins a slimming club and clashes with her sister, while Frank finds himself on the wrong side of the law accused of murder" --Container.